Deteksi Kontaminan Babi (Sus scrofa domesticus) dalam Olahan Sosis Menggunakan Gene Checker di Daerah Kota Medan - Ikhlasul Janu Nst; Zahratul Idami (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to detect the presence of porcine DNA (Sus scrofa domesticus) in sausage products circulating in Medan City using the Real-Time Polymerase Chain Reaction (Real-Time PCR) method with the GeneChecker instrument. The research employed a quantitative descriptive approach using five sausage samples collected from traditional markets, street vendors, and food stores through purposive sampling techniques. The research procedures included sample preparation, DNA extraction, master mix preparation, and amplification using porcine-specific primers. The test results were analyzed based on the Cycle Threshold (Ct) value on the FAM channel as the target for porcine DNA and the ROX channel as the internal control.The results showed that all samples had a Ct value of FAM = 0.00, indicating no detection of porcine DNA, while the Ct values of ROX ranged from 18–20, confirming that the internal control amplification process functioned properly. The positive control showed a valid Ct value, confirming that the PCR system and reagents operated optimally. In conclusion, all tested sausage samples showed no contamination of porcine DNA and were therefore considered negative for porcine DNA based on the Real-Time PCR analysis. The Real-Time PCR method using the GeneChecker instrument is effective and accurate for supporting halal verification of processed food products. Keywords: Porcine DNA, GeneChecker, Halal Authentication, Real-Time PCR, Sausage